How to Clean Up Mold - Hyun-Jeong Lee (EDIS)
FCS-3301, a 3-page illustrated fact sheet by Hyun-Jeong Lee, provides homeowners with basic guidance on assessing a mold problem, preparing for cleanup, and removal procedures, with links to other EDIS fact sheets for more detailed information.  Includes references. Published by the UF Department of Family Youth and Community Sciences, January 2009.